Reasons for Foreign Direct Investments in Countries of Transition - Lithuania - Tumėnas, Tomas (Ekonomika, 2000)
This article investigates reasons, which determined foreign direct investments into Lithuania over period 1990-2000 and factors affecting its further flow in the country for the period 2000-2010. The analysis is based in investment theory widely used intercountry studies method, where is presumed that driving force for foreign investments is growth of country’s economy. The development of Lithuania’s economy is compared with other Baltic State’s. The author underlines the major differences and factors affected Lithuania’s different economy’s situation in the region. According to the author the main factors influenced development of Lithuania’s economy as well as foreign direct investments were (1990-2000): economy’s heritage prior 1990; development of country’s financial-banking system; the quality of economy·s reforms implemented by the government; process of privatisation and relations with neighbouring countries. Further flow of FDI in Lithuania (2000-2010) would be affected by quality of economy’s reforms, especially how successfully the country will be able to join EU; sound development of financial-banking system; ability to get use from neighbouring relations and amount of FDI re-investments in country’s economy.